Scale, state and the city: Transformation of Diyarbakır, Suriçi region through the framework of spatial morphology and urban resilience - Berfin Eren; Mehmet Emin Şalgamcıoğlu (City and Environment Interactions)
Diyarbakır, located in southeastern Turkey, is known for its rich history and unique urban layout. The Suriçi region, which functions as the historic heart of Diyarbakır, has undergone significant changes over the years. In particular, developments over the last century have begun to reshape Suriçi’s spatial identity, which has evolved through historical processes influenced by spatial experiences. As a result, two distinct morphologies have emerged in the city: formation and deterioration. The shift between these two morphologies has fostered urban resilience. This paper introduces comprehensive, multi-faceted methods for measuring resilience based on space syntax theory and investigates resilience concepts through the relationships between space and society across various scales and time periods. Examining resilience at the urban scale through the street networks of different historical periods, produced via space syntax analysis, facilitates the formulation and analysis of patterns in urban movement, interactions, and past socio-economic activities. At the building scale, space syntax analysis reveals the spatial patterns of the altered morphological characteristics of traditional houses. It evaluates how these modified layouts reflect social, cultural, and political realities, and how they differ from the originally designed houses in spatial terms. The analysis of the city shows that while the overall position of the central area remains relatively stable, its morphology undergoes transformations. Traditional houses have retained certain features from their original designs; however, they have experienced modifications, such as subdivisions into multiple houses and changes in spatial arrangement. The study’s innovative integration of diachronic spatial analysis with socio-political context enriches the field by providing a more comprehensive model for assessing and forecasting urban resilience in historically significant areas, potentially guiding more effective preservation and development strategies.